Sustaining and expanding telehealth activity: Training requirements for Australian residential aged care front-line staff - Annie Banbury; Monica L. Taylor; Leonard C. Gray; Natasha Reid; Anthony C. Smith (Elsevier, 2023)
Objective: To identify the training needs of front-line aged care staff as perceived by senior clinicians and managers at selected residential aged care facilities (RACFs). Methods: A qualitative explorative designed study using semi-structured interviews with a convenience sample of RACF senior managers and nurses. A hybrid analysis approach using a framework deductive analysis followed by inductive analysis for sub-themes. Results: Four sub-themes emerged to sustain increased telehealth activity: technology knowledge and digital literacy skills, including understanding telehealth ecosystems and technical skills; evidence-based reviews and clinical frameworks for telehealth consultations to identify appropriate consultations and successful use cases; telehealth best practice guidelines and workflows including telehealth consultations protocols, communicating by videoconferencing, how to support families in attending telehealth consultations and optimal training models; and telehealth policy and legal guidance. Conclusion: Staff require comprehensive training to sustain and expand telehealth use in RACFs. Training should focus on knowledge, skills and competencies in using telehealth as well as the broad factors of policies and understanding ICT systems to support staffs' abilities and confidence. Innovation: This study provides innovative findings that identify key components and associated activities and resources for training RACF staff to ensure they have sufficient knowledge, competency, skills and confidence to integrate telehealth into care provision.